KERIS KAMARDIKAN - Kuntadi Wasi Darmojo (Ornamen, 2014)
Kamardikan keris, historically is a continuation of previous tangguh keris and part of the ancient relics in theform of material culture. As a material culture, Kamardikan keris has the form (dhapur), technique andfunction with its own characteristics and uniqueness. Kamardikan keris has a variety of dhapur among others:dhapur tangguh (classic-conventional) and dhapur creations (contemporary). Creativity arises due to internalfactors (personal) of self Kamardikan kris artists, and externally influenced by the surrounding environment.Individually, they act as creators and communicators who then receive a response from community supporters.As the indicator support is the emergence of a variety of organizations and educational institutions kerislovers of art which is the agent of the keris activity. Keris has an important position in the cultural traditions ofthe people of Java, but as a sign and symbol (meaning), which in the past was considered as the legitimateroyal power, now turned into a branding of existence and social status of person.Keywords: keris, kamardikan, creativity